Estudo químico e atividades biológicas do óleo essencial, extrato bruto e frações de Piper callosum Ruiz & Pav (Piperaceae) - (:unkn) unknown (Universidade Federal do Amazonas, 2020)
Piper callosum (Piperaceae) is a medicinal species endemic to the Amazon region, known as “electric oil”, used by the population as an aphrodisiac, astringent, digestive, antidiarrheal, local hemostatic, antileukorrheic, in mosquito bites. This species has still been little studied regarding its chemical profile and biological activity. Thus, the objective of this work was to evaluate yield, chemical profile, acaricidal and antioxidant activity of essential oil, crude extract and fractions of Piper callosum, in order to provide scientific data that contribute to the biological action of this Amazonian medicinal species. The yields of essential oils obtained in the rainy season (January 2018-2019) and dry season (October 2018-2019) were not influenced by the collection period. Phenylpronoid was the major chemical substance class in essential oils identified by CG-EM and its major constituents were safrole, α-pinene and β-pinene. The fumigant action showed that the mortality percentage of Suidasia pontifica increased with the time of exposure and concentration for the evaluated essential oils. As for the response concentrations (LC25% and LC50%), they were significant with p≤1.39.10-4 . The analysis of the chemical profile of the crude extract and fractions in test tubes, showed the presence of saponins, free steroids, flavanonol, flavanols, flobabenic tannins, xanthones and catechins. Through the DPPH free radical photocolorimetric method (2,2-diphenyl-1-picrylhydrazyl) it was possible to obtain CI50 of 89 and 91 µg/mL for the butanolic and hydroalcoholic fractions, respectively. The crude extract and fractions also showed corrected mortality greater than 50%, for Raoiella indica, in 24 h of exposure in the concentration of 5 mg/mL. For all samples and times evaluated, the slopes of the response lines (LC25% and LC50%) were significant with p≤8.14.10-04, indicating lethality in the population of R. indica. As for the isolation of chemical substances by High Performance Liquid Chromatography, it allowed the identification of chlorogenic, neochlorogenic acid and / or its stereoisomeric derivative. Therefore, the species P. callosum, becomes a promising source of secondary metabolites of interest to the food, cosmetics, perfumery, agrochemicals and other industries.
Keywords: Essências e óleos essenciais - Uso terapêutico; Essências e óleos essenciais; Antioxidantes; OUTROS; Metabólitos secundários; Raoiella indica; Suidasia pontifica; Antioxidante